Preservation and Conservation of Library Resources in Nigerian Libraries: A Review - Usiedo, Blessing Anegbemente; Kalu, Chidi Onuoha; Nworie, Josiah Chukwumaobi; Ibeh, Oluchi Bridget (Communicate: Journal of Library and Information Science, 2022)
Libraries in its quest for acquiring resources should bear in mind that there will be a need for the resources to be preserved for its effective use. Therefore, library resources preservation and conservation is one of the major functions of the library. This paper tends to review preservation and conservation of library resources in Nigeria. The paper discusses the concept of library resources as those materials, both print and non-print found in educational libraries which support curriculum and personal information needs. It also discusses damages to library resources, which includes the cause of deterioration of library resources such as internal or inherent vices and external agents. The paper equally talks about the main issues in preservation and conservation of library resources, in which preservation is seen as an activity in the library that encompasses all actions taken by the library or library staff to ensure the prolongation of life of resources kept in the library. Conservation on the other hand is a direct method of treatment in which an item is physically or chemically changed. The paper also outlines the challenges facing preservation and conservation of print library resources and techniques for preservation and conservation of library resources. Digital preservation of library resources were also discussed, including concept of digital preservation, objective of digital preservation, requirement of digital preservation, digitalization equipment and digital preservation techniques. The paper concludes that libraries should not only strive to acquire resources, but should ensure that the resources acquired are preserved and conserved in a usable condition for generations of users.